Motherland : Russia in the 20th century - Marples, David R. (Routledge, 2014)
Motherland tells the dramatic story of the rise and fall of the Soviet Union. From Lenin''s virtual coup in November 1917 to Boris Yeltsin''s ruthless takeover of power in 1991, the book culminates with a new view of the Yeltsin years.David Marples focuses on the evolution of Russia during the Soviet period, and the attempt to harness Russian nationalism to the avowed Soviet mission of promoting World Communism. Along the way heanalyses some of the more intensive historical debates and uncovers some of the myths perpetuated by state propaganda, especially those associated with the Great Patrio
Keywords: Soviet Union : History